2017
DOI: 10.1136/bmj.j1053
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure prophylaxis for infants exposed to HIV through breast feeding

Abstract: International audience

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…As lifelong maternal cART is now the WHO recommendation, these infant PrEP regimens are less likely to be used on a large scale. There are no clinical trials of maternal cART plus infant PrEP in the context of breastfeeding, although it has been suggested that this could be a feasible approach in resource‐poor settings where women may not have fully suppressed viral load and may be more likely to give medication to the infant than take it themselves .…”
Section: Neonatal Managementmentioning
confidence: 99%
“…As lifelong maternal cART is now the WHO recommendation, these infant PrEP regimens are less likely to be used on a large scale. There are no clinical trials of maternal cART plus infant PrEP in the context of breastfeeding, although it has been suggested that this could be a feasible approach in resource‐poor settings where women may not have fully suppressed viral load and may be more likely to give medication to the infant than take it themselves .…”
Section: Neonatal Managementmentioning
confidence: 99%
“…2-4 Thus, evaluation of the safety and efficacy of alternative strategies, such as infant prophylaxis, to reduce postnatal infection remains important. 5…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that ARVs to the mother (and/or infant) throughout the entire period of VT risk (pregnancy, delivery and the duration of breast feeding) are critical to prevent new infant infections [7, 8**, 911]. The Promoting Maternal and Infant Survival Everywhere (PROMISE) trial recently finally provided randomised trial evidence for the beneficial effect on early VT of maternal ART initiated during pregnancy compared to zidovudine (ZDV) prophylaxis in women with high CD4 counts [12**].…”
Section: Importance Of a Maximally Suppressive Regimen For Maternal Hmentioning
confidence: 99%